1989
DOI: 10.1095/biolreprod41.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor in Human Luteal Phase Endometrium1

Abstract: Platelet-activating factor (PAF; 1-O-alkyl-2-acetyl-sn-glycero-3-phosphorylcholine) is one of the most potent mediators of vascular permeability. PAF levels change in the rabbit endometrium just prior to implantation, which suggests that PAF may be a key substance transducing preimplantation embryonic signals. To study whether PAF was present in the human endometrium, and if so, to determine the cellular origin and hormonal regulation of endometrial PAF, specimens were obtained from 14 women (aged 23-42 yr) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Most uterine PAF activity was present within the endometrium. PAF was also found in human endometrial tissue, predominantly within the stromal cells of the endometrium [7]. In the current study, endometrial explants were used, and the possibility that the detected PAF originated from other cells within endometrium (e.g., endothelial cells, platelets, or polymorphonuclear leukocytes) cannot be excluded.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most uterine PAF activity was present within the endometrium. PAF was also found in human endometrial tissue, predominantly within the stromal cells of the endometrium [7]. In the current study, endometrial explants were used, and the possibility that the detected PAF originated from other cells within endometrium (e.g., endothelial cells, platelets, or polymorphonuclear leukocytes) cannot be excluded.…”
Section: Discussionmentioning
confidence: 84%
“…This is the first report of the release of PAF by the uterus in eutherian mammals. Alecozay et al [7] found that human stromal endometrial cells in culture only occasionally released small amounts of PAF into medium, even though significant concentrations of PAF were found within the corresponding cells. It should be noted, however, that those cultures were performed in medium 199 supplemented with 10% fetal calf serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also produced by a number of nonimmune cells such as endothelial (9), vascular, muscle (43), glomerular (13) and endometrial cells (4,5,7,45). PAF plays a role in many reproductive events (16), including ovulation (1), fertilization (27), implantation and early development of embryo (28).…”
Section: Introductionmentioning
confidence: 99%
“…PAF plays a role in many reproductive events (16), including ovulation (1), fertilization (27), implantation and early development of embryo (28). PAF has been determined in the uterus of rats (45), rabbits (5), dogs (35) and humans (4). It plays a significant role in mammalian reproduction (29,32).…”
Section: Introductionmentioning
confidence: 99%